Additive Effects of the Risk Alleles of PNPLA3 and TM6SF2 on Non-alcoholic Fatty Liver Disease (NAFLD) in a Chinese Population - Wang, Xiaoliang; Liu, Zhipeng; Wang, Kai; Wang, Zhaowen; Sun, Xing; Zhong, Lin; Deng, Guilong; Song, Guohe; Sun, Baining; Peng, Zhihai; Liu, Wanqing (Frontiers in Genetics, 2016)
Recent genome-wide association studies (GWASs) identified that variants in or near PNPLA3, NCAN, GCKR, LYPLAL1, TM6SF2 were significantly associated with nonalcoholic fatty liver disease (NAFLD) in multiple ethnic groups. Studies on their impact on NAFLD in Han Chinese is still limited. In this study, we examined the relevance of these variants to NAFLD in a community-based Han Chinese population and further explored their potential joint effects on NAFLD. Six single nucleotide polymorphisms (SNPs) (PNPLA3 rs738409, rs2294918, NCAN rs2228603, GCKR rs780094, LYPLAL1 rs12137855, and TM6SF2 rs58542926) identified in genome-wide analyses previously to be associated with NAFLD were genotyped in 384 NAFLD patients and 384 age and gender-matched healthy controls. We found two out of the six polymorphisms, PNPLA3 rs738409 (OR=1.52, 95%CI: 1.19-1.96; P = 0.00087) and TM6SF2 rs58542926 (OR=2.11, 95%CI: 1.34-3.39; P = 0.0016) were independently associated with NAFLD after adjustment for the effects of age, gender and BMI. We also found that GCKR rs780094 showed a marginal association with NAFLD (OR=1.23, 95%CI: 0.99-1.53; P = 0.068). Our analysis further demonstrated a strong additive effects of the risk alleles of PNPLA3 and TM6SF2 with an overall significance between the number of risk alleles and NAFLD (OR=1.64, 95%CI: 1.34-2.01; P = 1.410-6). The OR for NAFLD increased in an additive manner, with an average increase in OR of 1.52 per one risk allele increase. Our results confirmed the PNPLA3 and TM6SF2 variants were the most significant risk alleles for NAFLD in Chinese population. Genotyping the two genetic risk factors may help identify individuals with the highest risk for NAFLD.